The Effect of Yoga on Quality of Sleep; Literature Review - Firdaus, Fidya Anisa; Noviati, Elis; Kusumawaty, Jajuk; Ariyanto, Heri; Khaerunnisa, Reffi Nantia (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Sleep Disorders are a public health problem in the community. One of the cheap interventions without side effects that can be used is yoga. yoga involve body awareness and self regulation techniques that use psychophysical. Aim: To evaluate the effect of yoga on sleep quality in people with sleep disorders with or without medical conditions. Search Metod: Systematic review use data were identified from 11 journal database including PubMed, Cochrane Library, Science Direct, JSTOR, Willey Online Library, Springer, Sage Journal and Taylor Franciss Online with keywords: Yoga, Quality of Sleep and Randomized Controlled Trial. The inclusion criteria in this study are articles published in 2009 - 2020, available in full text, articles in English, with human subjects, RCT design. The netted articles are 11 experimental research articles which are then analyzed using PRISMA. Result: Eleven Randomized Controlled Trials yoga have a significant effect on the sleep quality of patients with sleep complaints with or without medical conditions. With a total of 510 participants in the intervention group and 498 in the control group. Conclusion: Yoga efektive increased quality of sleep people sleep disorder with or without medical conditions.and can be used by nurses to promote yoga to improve sleep quality.